Economic feasibility of modifications to the design of transport aircraft - IGNATYEVS, Sergeys; MAKUSHKIN, Sergey A.; SPIVAKOVSKYY, Sergiy (INCAS bulletin, 2021)
The relevance of the subject matter is conditioned by the need to fully justify the implementation of modifications to the structures of transport aircraft from an economic standpoint, in order to save money during their construction and improve the functioning of the system for planning further design developments in this line. The purpose of this study is to establish a coherent model of the economic feasibility of aircraft modifications, which allows effectively solving the issues of cost savings in their design and subsequent launch into mass production and operation. The leading approach in this study is a combination of analytical research of the issues of transport aircraft modification with empirical research of the economic feasibility of such measures, in the context of creating a coherent concept of the need for a set of measures to improve the structure of air transport. The findings indicate the presence of a clear relationship between a wide range of parameters that determine the indicators of economic feasibility of modernizing transport aircraft, as well as significant economic advantages of a high-quality modification of the aircraft design.